Antimicrobial Resistance Profile and Molecular Screening of blaKPC Gene among Clinical Isolates of Pseudomonas aeruginosa from a Tertiary Care Hospital, Nepal - Adhikari, Ram Prasad; Khanal, Laxmi Kant; Sapkota, Jyotshna; Pandey, Ritu; Sah, Anil Kumar; Khadka, Shusila; Rai, Shiba Kumar (Nepal Medical College Journal, 2025)
Pseudomonas aeruginosa is a major opportunistic pathogen with increasing antimicrobial resistance, creating significant treatment challenges in hospital settings. This study aimed to determine the antimicrobial resistance profile of P. aeruginosa and screen for the blaKPC gene among meropenem-resistant isolates. A descriptive cross-sectional study was conducted from December 2021 to May 2022, yielding 75 non-duplicate isolates identified through standard microbiological methods; antimicrobial susceptibility testing was performed using the Kirby- Bauer technique, and 17 meropenem-resistant isolates underwent PCR for blaKPC detection. Sputum (33.33%) and pus (29.33%) were the most common specimen sources, and multidrug resistance was observed in 54.7% of isolates, particularly among inpatients and ICU cases. High-rate resistance to ceftazidime and piperacillin was noted, while carbapenem resistance remained moderate (21-23%). None of the meropenem-resistant isolates carried the blaKPC gene, indicating alternative carbapenem resistance mechanisms. These findings highlight a substantial burden of MDR P. aeruginosa and underscore the need for ongoing surveillance and strengthened infection control practices.